Dynamic De/Centralization in Germany, 1949–2010. Issue 1 (18th September 2017) - Kaiser, André; Vogel, Stephan
Abstract: As part of the project Why Centralization and Decentralization in Federations?, this article measures dynamic de/centralization in Germany since 1949 and seeks to explain the patterns observed. It shows stability in numerous policy fields as well as an overall marked centralization over time, especially in the fiscal and administrative spheres. The principal instrument of dynamic de/centralization has been the enactment of legislation in fields of shared responsibility, with constitutional change also being important. In the 1950s and 1960s, an incremental centralization occurred as political and administrative elites strongly favored uniform living conditions. In a context of Keynesian interventionism and a broad consensus about social planning, the Great Fiscal Reform of 1969 amplified this centralizing trend. The East-West unification of 1989-1990 increased the economic and fiscal heterogeneity of the Länder and challenged the cultural norm of uniformity. The resulting federalism reforms of 2006 and 2009 blended decentralizing and centralizing measures.